First record of Tabanus lunatus from Iran - Samiei, Avat; Tavassoli, Mousa; Moradi, Salah (ENTOMOLOGIA HELLENICA, 2016)
In August 2015, the species Tabanus lunatus Fabricius, 1794 (Diptera: Tabanidae) was recorded for the first time from Iran. Two females were collected in Nazlo area near Urmia. Information on its morphology and distribution is given